“Protección del desarrollo de productos elaborados en la carrera de Agroindustria a través del secreto industrial de la bebida refrescante y de la cerveza artesanal a partir de aguamiel de agave (agave americana l)”. - Tipantuña Guaman, Paola Judith (2024)
The present work aims to protect by means of the industrial secret, the products developed while in the research, “Identification and physicochemical characterization of agaves for agro-industrial purposes in Latacunga canton”, conducted in 2020 at the Agro-industry Major of the Technical University of Cotopaxi with the following topics: STABILIZATION OF A REFRESHING BEVERAGE FROM AGAVE HONEY WATER (American Agave L.); EVALUATION OF THE INCORPORATION OF HONEY WATER (American Agave L.) AND AROMATIC PLANTS IN BEER MAKING, for this, the most important information available in the university repository was compiled including the formulation, the methodology, flow diagrams, and matter balance for each product's process for their respective protocolization. For this, legal advice from a specialized lawyer knowledgeable in intellectual property procedures, who managed the necessary legal process for the appropriate registration. This measure has been necessary to assure the correct handling of procedures and to safeguard the university's interests in the registration process. During the process, the information gathered for the two products was executed, protocolization and notarization at the Third Notary of Latacunga canton, subsequently, a request was submitted to “SENADI” (National Service of Intellectual Rights) for the registration process of the products developed in the Agro-industrial Major, giving response to the protection of the industrial secret to the university while obtaining absolute ownership of the legal rights over the Refreshing Beverage and Craft Beer made from Agave Honey Water (American Agave L.). This ownership allows managing these products according to the academic and commercial needs that may arise in the future. This initiative does not only strengthen the institution's positioning in the academic and scientific fields but also contributes to the country's economic and social advancement by promoting the protection and valorization of natural and cultural resources.